Relationship between socio-environmental factors, personal factors, fruits and vegetables intake among adolescents in Kelantan - Yeng, Wong Siew (Universiti Sains Malaysia, 2016)
Low fruits and vegetables consumption is a persistent problem worldwide that has been linked with various chronic diseases. However, there is limited knowledge on factors that influence fruits and vegetables consumption in Malaysia, especially for the adolescent group. Hence, the objective of this study was to examine the relationship between socioenvironmental factors, personal factors and adolescent’s fruits and vegetables consumption in Kelantan, Malaysia. A total of 223 respondents were randomly selected from 5 secondary schools in Kelantan. Data were collected by self-report questionnaire and height and weight was measured to calculate Body Mass Index (BMI) of respondents. Out of expectation, more than half of the respondents (69.5%) consumed fruits and vegetables >5 times per day. Among the respondents, 68.2% were in normal body weight status. The prevalence of overweight and obesity were 11.7% and 10.8%, respectively. In categorical analysis, no significant associations were observed between BMI and fruits consumption (x2 - 0.92, p>0.05) and also BMI and vegetables consumption (x2=0.27, p>0.05). In correlation analysis, socio-environmental factors including home availability of fruits and vegetables, parental modeling, parental support for healthy eating, peer support for healthy eating and family meal patterns as well as personal factors including health or nutrition attitudes and weight or body concerns showed significant relationship with fruits and vegetables consumption. However, taste preferences inconsistent with other studies, did not showed significant correlation with fruits and vegetables consumption (r=-0.03, p>0.05). In conclusion, nutrition interventions could incorporate socio-environmental factors as well as personal factors to improve fruits and vegetables consumption among adolescents in Malaysia.